Automatic defense against zero-day polymorphic worms in communication networks - Mohammed, Mohssen, 1982-; Pathan, Al-Sakib Khan (Boca Raton, Florida : CRC Press, 2013)
"A computer worm is a kind of malicious program that self-replicates automatically and quickly to compromise the security of a computer network. A polymorphic worm is able to change its payload in every infection attempt thereby forcing constant changes to ward off the attacks. Whenever a novel worm is detected in the Internet, the common approach is that the experts from security community analyze the worm code manually and produce a signature. The alternative approach is to find a way to automatically generate signatures that are relatively faster to generate and are of acceptable good quality. This book focuses on how we can automatically generate signatures for unknown polymorphic worms"--
ch. 1. The fundamental concepts -- ch. 2. Computer networking -- ch. 3. Intrusion detection and prevention systems (IDPSs) -- ch. 4. Honeypots -- ch. 5. Internet worms -- ch. 6. Reading resources on automated signature generation systems -- ch. 7. Signature generation algorithms for polymorphic worms -- ch. 8. Zero-day polymorphic worm collection method -- ch. 9. Developed signature generation algorithms.
"An Auerbach book."
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Computer viruses; Computer algorithms; Computer networks -- Security measures; Machine theory; Electronic books